Advancing hard carbon anode for sodium-ion batteries: Mechanisms and optimization strategies - Yujie Guo; Shun Ji; Jinlin Wang; Ziyi Zhu; Yanjia Zhang; Jie Xiao; Feng Liu; Xiaoyuan Zeng (Nano Research Energy)
The development of sodium-ion battery technology has played a pivotal role in driving innovation within the energy storage field. Over the past several years, ranging from laboratories to industrial practice, this field has achieved phased results. However, current sodium-ion battery systems are hard-pressed to meet the increasingly stringent demands of the market for high energy density, long cycle life, and rapid charging and discharging. In recent years, hard carbon anodes have attracted the attention of numerous researchers due to their unique structural characteristics and sodium-storage potential. This review systematically and comprehensively examines the working principles and compositions of sodium-ion battery, critically evaluates common anode materials, and analyzes the sodium storage mechanism in hard carbon. Moreover, this review comprehensively summarizes multi-dimensional performance improvement strategies, such as morphology engineering, heteroatom functionalization, defect engineering, and electrolyte optimization, and deeply explores future development directions of sodium-ion batteries and hard carbon anode, offering more valuable insights and a solid theoretical foundation for promoting the development of hard carbon anode technology and accelerating the commercialization process of sodium-ion battery.